Методы распараллеливания циклов - Полуян, Ю.А.; Чемерис, А.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
This paper deals with ways to find data dependences in nested loops. The algorithms of loop transformations permitting nested loops with loop-carried dependences to be parallelized are presented.